A boy named Isamu : a story of Isamu Noguchi - Yang, James, 1960- (Viking, 2021)
Imagines a day in the boyhood of Japanese American artist, Isamu Noguchi, while wandering through an outdoor market, through the forest, and then by the ocean, seeing things Isamu sees through the eyes of a young artist.